Integrasi Kecerdasan Buatan dan Strategi Bisnis dalam Transformasi Digital - Maria Atik Sunarti Ekowati; Rousyati; Ahmad Fauzi; Pudji Widodo (LPPM STMIK El Rahma Yogyakarta, 2026)
Digital transformation has become a critical driver of organizational competitiveness in today’s disruptive economic environment. This study examines the integration of Artificial Intelligence (AI) with digital business strategies across the e-commerce, fintech, education, healthcare, and manufacturing sectors. A multi-case quantitative approach was employed using 250 observations collected over a ten-month period from organizational information systems, customer satisfaction surveys, and operational performance indicators. Data analysis was conducted using Random Forest and Support Vector Machine (SVM) algorithms to predict business strategy effectiveness, while multiple regression analysis was used to examine relationships among key variables. The results indicate significant improvements in productivity (24.5%), operational efficiency (24.1%), customer satisfaction (24.2%), and return on investment (27.5%). The multiple regression model achieved an R² value of 0.82, while the Random Forest model attained a predictive accuracy of 91%. The study contributes by proposing an AI–business strategy integration framework that extends the Resource-Based View and Strategic Alignment perspectives. Practical implications include supporting managerial decision-making in AI investment allocation, enhancing data analytics capabilities, and developing predictive customer relationship management (CRM) systems. The novelty of this research lies in combining quantitative analysis, data simulation, and predictive modeling to support sustainable digital transformation.